Contextualisation and Mission Training : Engaging Asia's Religious Worlds - Tan, Loun Ling; Tan, Kang San; Ingleby, Jonathan (Book collections on Project MUSE., 2014)
"Offers 'contextual frameworks' and 'explorations' in order to enhance deeper engagement with the complexity of Asian social, cultural and religious systems. When we take contextualisation theories seriously, how does it change the way we prepare and train cross cultural workers? Without claiming definitive answers, this book seeks to raise pertinent and controversial issues to do with some of the challenges facing the Asian church in engaging with the religious contexts of Asia"--Page 4 of cover.